The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1203/00006450-199710000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Reflex Is Not Responsible for Changes in Airway and Lung Tissue Mechanics Due to Vascular Engorgement in Young Piglets

Abstract: Eleven open-chest piglets were studied to examine the effects of vascular engorgement on partitioned airway and lung tissue mechanics, and to investigate the role of vagal denervation on lung function during engorgement. Alveolar pressure was measured using alveolar capsules. Pulmonary elastance (EL) and resistance (RL), airway (Raw), and tissue (Vti) resistance were calculated during mechanical ventilation. Acute fluid administration with polygeline (10 mL/kg boluses up to a total of 30 mL/kg) resulted in an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…Increases in left atrial pressure as a result of the transient obstruction of pulmonary venous return in dogs was well correlated with reductions in pulmonary compliance [9,10]. In contrast, varying pulmonary arterial flow did not cause significant changes in respiratory mechanics [11]. Pulmonary hypertensive crises are associated with increases in pulmonary arterial resistance, possibly increases in pulmonary venous resistance, as well as reductions in pulmonary blood flow and pulmonary capillary blood volume.…”
Section: Discussionmentioning
confidence: 91%
“…Increases in left atrial pressure as a result of the transient obstruction of pulmonary venous return in dogs was well correlated with reductions in pulmonary compliance [9,10]. In contrast, varying pulmonary arterial flow did not cause significant changes in respiratory mechanics [11]. Pulmonary hypertensive crises are associated with increases in pulmonary arterial resistance, possibly increases in pulmonary venous resistance, as well as reductions in pulmonary blood flow and pulmonary capillary blood volume.…”
Section: Discussionmentioning
confidence: 91%
“…This qualitative observation was confirmed by Hogg et al (14), who demonstrated a tendency to a positive correlation between blood flow and lung expansion. Subsequent studies involving lung function measurements have provided further evidence that pulmonary vascular congestion leads to an increase in lung size and/or stiffness at low lung volume by overstretching the capillary network in the alveolar wall (10,29,36,37). It seems plausible to adapt this mechanism to explain the marked differences in the parenchymal parameters between the perfused and unperfused lungs at low lung volumes on the basis of the stabilizing role of the filled pulmonary capillaries in the maintenance of the physiological alveolar architecture.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous clinical (3,7,9,11,20,27) and experimental studies (29,36,37) have demonstrated that elevation of the pulmonary blood flow (7,20,27) and/or pressure (3,11,29,36,37) leads to a deterioration of the lung function via a decrease in functional residual capacity (FRC) (7) and/or stiffening of the alveolar wall (40). Although the qualitative examinations performed by von Basch (38a) in 1889 suggested that not only congestion, but also pulmonary hypoperfusion, can alter the lung configuration, few data are available concerning the changes in the mechanical conditions of the lungs during hypoperfusion or the complete absence of pulmonary perfusion (21,25,29,35).…”
mentioning
confidence: 99%
“…Conversely, a high Ppa has been demonstrated to play a major role in determining the mechanical properties of the lungs, since changes were observed only when Ppa was elevated (2,15,27,28). Finally, other authors observed abnormal lung function only when an increased Q p was associated with an elevated Ppa (3,20).…”
mentioning
confidence: 92%
“…Some investigations have revealed a clear correlation between an elevated Ppa and the subsequent changes in the mechanical properties of the lungs (2,13,23,27,28), although the increases in Ppa were always associated with increases in pulmonary venous pressures in those investigations. Other studies failed to detect any change in lung function in the presence of an elevated Ppa (3,6,7,11,22,26).…”
Section: Pulmonary Hemodynamics Affect Lung Mechanicsmentioning
confidence: 99%